PENGAWASAN UNIT APRON MOVEMNT CONTROL (AMC) TERHADAP DISIPLIN PENGGUNA JASA DI BANDAR UDARA KOMODO LABUAN BAJO - Miftakhul Fian Saputra; Irwina Meilani (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Social media marketing is a means to fulfill all needs. Social media marketing is used in Sriwijaya Air by promoting tickets through social media so that people know the information. This study aims to determine the effect of social media marketing on ticket sales for Sriwijaya Air and to determine how much influence social media marketing has on ticket sales for Sriwijaya Air at Ahmad Yani Airport in Semarang. This research is a quantitative study using non probability sampling, with a sample size of 100 passengers and an error rate of 5%. The data collection process uses a questionnaire and the data analysis used is simple linear regression and the coefficient of determination then the data processing uses the SPSS 26 application. The results of this study indicate that the Social Media Marketing variable has a significant effect on Sriwijaya Air ticket sales at Ahmad Yani Airport Semarang with sig (0.000 <0.05). Furthermore, the coefficient of determination is obtained as much as 0.577, this means that the influence of Social Media Marketing on ticket sales of Sriwijaya Air airline is 57.7%.